2023
DOI: 10.1101/2023.11.22.567924
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting phage-bacteria interactions at the strain level from genomes

Baptiste Gaborieau,
Hugo Vaysset,
Florian Tesson
et al.

Abstract: Predicting how phages can selectively infect specific bacterial strains holds promise for developing novel approaches to combat bacterial infections and better understanding microbial ecology. Experimental studies on phage-bacteria interactions have been mostly focusing on a few model organisms to understand the molecular mechanisms which makes a particular bacterial strain susceptible to a given phage. However, both bacteria and phages are extremely diverse in natural contexts. How well the concepts learned f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 91 publications
0
14
0
Order By: Relevance
“…Previous results have shown that adaptive mutations impacted the host-interaction subunits proteins, such as capsides or spikes proteins for microvirid bacteriophages (Sackman et al, 2017), ΦX174 (B X174 (Bull et al, 1997;Crill et al, 2000;Pepin et al, 2008) and receptor binding proteins in the RNA virus ΦX174 (B 6 (Duffy et al, 2006;Ferris et al, 2007) as well as almost hundred Caudoviricetes (Gaborieau et al, 2023). Interestingly, we didn't observe any adaptive mutation in the gene coding for pb5 the major receptor binding proteins (RBP), that commits the phage to infection, triggering cell wall perforation and DNA ejection through a non-reversible interaction with…”
Section: Discussionmentioning
confidence: 99%
“…Previous results have shown that adaptive mutations impacted the host-interaction subunits proteins, such as capsides or spikes proteins for microvirid bacteriophages (Sackman et al, 2017), ΦX174 (B X174 (Bull et al, 1997;Crill et al, 2000;Pepin et al, 2008) and receptor binding proteins in the RNA virus ΦX174 (B 6 (Duffy et al, 2006;Ferris et al, 2007) as well as almost hundred Caudoviricetes (Gaborieau et al, 2023). Interestingly, we didn't observe any adaptive mutation in the gene coding for pb5 the major receptor binding proteins (RBP), that commits the phage to infection, triggering cell wall perforation and DNA ejection through a non-reversible interaction with…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial receptors are the major determinant of phage susceptibility, even more than internal phage resistance mechanisms 1 . Hence, phages have evolved different strategies to overcome the diversity of phage receptors.…”
Section: Discussionmentioning
confidence: 99%
“…When infecting a bacterial host, the phage receptor binding proteins recognize the surface receptor of the bacterial host. The specificity of this initial phage-host interaction ensures the infection of proper hosts, and receptors have been suggested as the major determinant of the host range of phages 1 . On the phage side, most characterized phages typically use a single receptor binding protein to recognize their bacterial host.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the impact of different defense systems in naturally occurring Vibrio isolates has revealed that a rapid turnover of a few mobile genetic elements encoding defense systems can completely alter their susceptibility to phages 16,17 . Ongoing research is delving into the broader phylogenetic scale to explore the role of antiphage systems and their potential implications for phage therapy strategies 18,19 . Furthermore, examples indicate that antiphage systems can be co-regulated and operate synergistically in multi-layered defense strategies 20 .…”
Section: Introductionmentioning
confidence: 99%